Thermal and solutal energy transport analysis in entropy generation of hybrid nanofluid flow over a vertically rotating cylinder - Ahmad, Shafiq; Ahammad, N. Ameer; Khan, Muhammad Naveed; Algehyne, Ebrahem A.; Tag-Eldin, Elsayed; Gepreel, Khaled A.; Guedri, Kamel; Galal, Ahmed M. (Frontiers in Physics, 2022)
An investigation of an axisymmetric mixed convective boundary layer flow of silver-titanium dioxide/water ( ) hybrid nanofluid towards vertically and rotating stretching cylinder with entropy generation is explored in the present research work. The Cattaneo-Christov theory and joule heating effect is taken to analyze the thermal energy features. Moreover, the magnetic impact and convective boundary conditions on the vertical surface also considered in the current investigation. The developing equations for momentum, energy and entropy generation are modelled and by the usage of similarity variables to transform into the system of nonlinear ODEs (ordinary differential equations). The solutions of nonlinear ODEs are obtained numerically by the assistance of BVP4C MATLAB built-in scheme. The graphical consequence and physical reasoning are discussed on the velocity, temperature, and concentration profiles by challenging way. It is noteworthy that strong estimation of buoyancy ratio and mixed convection parameter enhances axial velocity, but swirl velocity diminishes. The fluid temperature and concentration both are diminished with thermal and solutal stratification effects. It is also seen that thermal Biot and Eckert number enhances the temperature distribution. Further, the Reynold number improves the entropy generation.